2018
DOI: 10.1142/s0218127418501559
|View full text |Cite
|
Sign up to set email alerts
|

On the Entropy Points and Shadowing in Uniform Spaces

Abstract: We introduce and study the topological concepts of entropy points, expansivity and shadowing property for dynamical systems on noncompact nonmetrizable spaces, which generalize the relevant concepts for metric spaces. We also obtain various properties on uniform entropy on noncompact nonmetrizable spaces. The main result is a theorem which yields a relation between topological shadowing property and positive uniform entropy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…DOI: 10.24193/mathcluj.2024. 1.02 results about equicontinuity to the uniform spaces; Das et al [13] generalized spectral decomposition theorem to the uniform spaces; The authors of [3] generalized concepts of entropy points, expansivity and the shadowing property for dynamical systems on uniform spaces and obtained a relation between the topological shadowing property and the positive uniform entropy. For more results on properties of dynamical systems in purely topological terms, one is referred to [2,14,22,[26][27][28].…”
Section: Generalized Many Knownmentioning
confidence: 99%
“…DOI: 10.24193/mathcluj.2024. 1.02 results about equicontinuity to the uniform spaces; Das et al [13] generalized spectral decomposition theorem to the uniform spaces; The authors of [3] generalized concepts of entropy points, expansivity and the shadowing property for dynamical systems on uniform spaces and obtained a relation between the topological shadowing property and the positive uniform entropy. For more results on properties of dynamical systems in purely topological terms, one is referred to [2,14,22,[26][27][28].…”
Section: Generalized Many Knownmentioning
confidence: 99%
“…Then, we [15] proved that a point transitive dynamical system is either sensitive or almost equicontinuous. Recently, we [3,4] generalized concepts of entropy points, expansivity and shadowing property for dynamical systems to uniform spaces and obtained a relation between topological shadowing property and positive uniform entropy. Shah et al [13] showed that a dynamical system on a totally bounded uniform space which is topologically shadowing, mixing, and topologically expansive has the topological specification property.…”
Section: Introductionmentioning
confidence: 99%
“…The notion of positively expansive maps were introduced in uniform spaces [33,16]. There are more results of dynamical systems on uniform spaces in [3,36].…”
Section: Introductionmentioning
confidence: 99%